2001
DOI: 10.1177/107110070102200507
|View full text |Cite
|
Sign up to set email alerts
|

Results of Operative Fixation of Unstable Ankle Fractures in Geriatric Patients

Abstract: It is widely accepted that operative fixation of unstable ankle fractures yields predictably good outcomes in the general population. The current literature, however reports less acceptable results in the geriatric population age 65 years and older. The current study analyzes the outcome of the surgical treatment of unstable ankle fractures in patients at least 65 years old. Twenty three patient over 65 years old were surgically treated after sustaining 21 (91%) closed and 2 (9%) open grade II unstable ankle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 17 publications
2
34
1
1
Order By: Relevance
“…Most are stable fractures that are easily treated nonoperatively. Surgical treatment of the unstable ankle fracture generally is associated with improved outcomes, even in geriatric patients 2,3 . The overall rate of complications after open reduction and internal fixation of ankle fracture varies between 5% and 40%, depending on the population investigated 4 .…”
mentioning
confidence: 99%
“…Most are stable fractures that are easily treated nonoperatively. Surgical treatment of the unstable ankle fracture generally is associated with improved outcomes, even in geriatric patients 2,3 . The overall rate of complications after open reduction and internal fixation of ankle fracture varies between 5% and 40%, depending on the population investigated 4 .…”
mentioning
confidence: 99%
“…This appears to be especially true since data have shown that the use of surgery for injuries of the foot and ankle in the elderly individuals has similar complications and outcomes to those seen in younger patients. [11][12][13][14][15][16][17][18][19][20][21][22][23][24]28,32,33,38,39 The surgical approaches and fixation methods used to manage these injuries are similar to the principles used in the surgical treatment of younger patients, with some slight modifications. With the development of locking plate technology along with improved surgical approaches and techniques, the concerns for providing fixation to pathologic bone have been lessened.…”
Section: Discussionmentioning
confidence: 99%
“…24 This has been validated by other studies 22,23 and has demonstrated similar findings for the management of ankle fractures in the elderly individuals. [11][12][13][14][15][16][17][18][19][20][21] Using this as a guide, such complications as the development of post-traumatic arthritis may be higher in the elderly patients, perhaps due to preexisting arthritis, but good outcomes can be obtained with very few patients needing an arthrodesis as a salvage for their management of pain. 24 A second problem is in dealing with complications associated with patient comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations